2020
DOI: 10.1055/s-0040-1705115
|View full text |Cite
|
Sign up to set email alerts
|

Antiphosphatidylserine/Prothrombin Antibodies: An Update on Their Association with Clinical Manifestations of Antiphospholipid Syndrome

Abstract: Objective The aim of the study is to perform a systematic review on the recent available evidence on antiphosphatidylserine/prothrombin (aPS/PT) antibodies and their association with clinical manifestations of the antiphospholipid syndrome (APS). Methods A detailed literature search was applied a priori to Ovid MEDLINE, In-Process and Other Non-Indexed Citation 2012 to present and to abstract from EULAR and ACR/ARHP Annual Meetings (2012–2019). Results Data from 2,901 patients, 587 diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…Among the extra criteria aPL, testing for aPS/PT antibodies has been proposed as an additional tool to be considered when investigating a patient suspected of having antiphospholipid syndrome, particularly in the absence of routine aPL positivity, 29,30 or as a part of risk assessment strategies. 31 A recent systematic review 32 Our work has some limitations that need to be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the extra criteria aPL, testing for aPS/PT antibodies has been proposed as an additional tool to be considered when investigating a patient suspected of having antiphospholipid syndrome, particularly in the absence of routine aPL positivity, 29,30 or as a part of risk assessment strategies. 31 A recent systematic review 32 Our work has some limitations that need to be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Among the extra criteria aPL, testing for aPS/PT antibodies has been proposed as an additional tool to be considered when investigating a patient suspected of having antiphospholipid syndrome, particularly in the absence of routine aPL positivity, 29,30 or as a part of risk assessment strategies 31 . A recent systematic review 32 that analyzed the studies on aPS/PT and their correlation with clinical manifestations of antiphospholipid syndrome from 2012 to 2019 showed a statistically significant association between any pregnancy morbidity and aPS/PT IgG/IgM positivity (mean OR 10.6 [95% CI 3.54‐35.38], P < .05).…”
Section: Discussionmentioning
confidence: 99%
“…33 A recent systematic review showed a strong association between aPS/PT aPL and clinical manifestations of APS, with a high association with LAC. 34 However, this needs to be validated in a large multicenter study.…”
mentioning
confidence: 99%
“…Various studies have demonstrated the clinical utility of aPS/PT in the diagnosis of APS, especially in the absence of antibodies included in the diagnostic criteria [ 15 , 61 , 62 ]. Likewise, several studies have indicated a strong association between aPS/PT antibodies and obstetric morbidity [ 20 , 59 , 63 ]. However, they have not yet been included as classification criteria for APS because some drawbacks in the studies, such as the small size on which these data are based, the methodological differences in their design, the lack of standardization in their determination and the contradictory results related to their association with the APS.…”
Section: Discussionmentioning
confidence: 99%